Desiccation tolerance of Sphagnum revisited: a puzzle resolved. (6th November 2013) - Hájek, T.; Vicherová, E.; Adams, W.
Abstract As ecosystem engineers, Sphagnum mosses control their surroundings through water retention, acidification and peat accumulation. Because water retention avoids desiccation, sphagna are generally intolerant to drought; however, the literature on Sphagnum desiccation tolerance (DT) provides puzzling results, indicating the inducible nature of their DT. To test this, various Sphagnum species and other mesic bryophytes were hardened to drought by (i) slow drying; (ii) ABA application and (iii) chilling or frost. DT tolerance was assessed as recovery of chlorophyll fluorescence parameters after severe desiccation. We monitored the seasonal course of DT in bog bryophytes. Under laboratory conditions, following initial de‐hardening, untreated Sphagnum shoots lacked DT; however, DT was induced by all hardening treatments except chilling, notably by slow drying, and in Sphagnum species of the section Cuspidata. In the field, sphagna in hollows and lawns developed DT several times during the growing season, responding to reduced precipitation and a lowered water table. Hummock and aquatic species developed DT only in late autumn, probably as a response to frost. Sphagnum protonemata failed to develop DT; hence, desiccation may limit Sphagnum establishment in drier habitats with suitable substrate chemistry. Desiccation avoiders among sphagna form compact hummocks or live submerged; thus, they do not develop DT in the field, lacking the initial desiccation experience, which is frequent in hollow and lawn habitats. We confirmed the morpho‐physiological trade‐off: in contrast to typical hollow sphagna, hummock species invest more resources in water retention (desiccation avoidance), while they have a lower ability to develop physiological DT.